EXPLOASI FINANCIAL INCLUSION MODELS UNTUK UMKM KOTA TASIKMALAYA - Yuniar, Evilia Sri; Fauziah Oktaviani, Nita (LP2M Universitas Perjuangan Tasikmalaya, 2025)
This study aims to determine the role of financial literacy, business models on financial inclusion and whether financial literacy is able to mediate business models on financial inclusion. The research method used is quantitative descriptive with the Structural Equation Model (SEM) analysis tool which is an analysis technique that allows testing a series of relationships simultaneously. The results of the study show 1) There is a significant influence of business models on financial inclusion of MSMEs in the East Priangan Region, 2) There is a significant influence of business models on financial literacy of MSMEs in the East Priangan Region, 3) There is a significant influence of financial literacy on financial inclusion of MSMEs in the East Priangan Region, 4) business models have an effect on financial inclusion with the mediation of financial literacy of MSMEs in the East Priangan Region. The results of this study can be concluded that the financial literacy variable can mediate business models on financial inclusion.